CBIO-23. PROXIMITY-DEPENDENT BIOTIN IDENTIFICATION (BIOID2) INDICATES MEMBRANE TRAFFICKING AND VESICLE TRANSPORT AS A POTENTIAL NOVEL FUNCTION OF EXTRACELLULAR SIGNAL-REGULATED KINASE 5 (ERK5). (9th November 2020) - Stanton, Ann-Catherine; Koller, Antonius; Koncar, Robert; Golbourn, Brian; Halligan, Katharine; Halbert, Matthew; Mack, Stephen; Pollack, Ian; Agnihotri, Sameer
Abstract: INTRODUCTION: Pediatric High-Grade Gliomas (PHGG), which include Diffuse Midline Gliomas (DMG), are a leading cause of brain tumor death in children. Our recent work has identified extracellular signal-regulated kinase 5 (ERK5) as a critical mediator of cell survival in DMG, as ERK5 knockdown decreases cell proliferation and extends survival time in orthotopic xenograft mice. Further investigation into the structure of ERK5 shows that it has a kinase domain and, unlike other ERKs, a transactivation domain, and both are important for promoting cell proliferation. HYPOTHESIS AND METHODS: We hypothesize that identifying interactors and substrates of ERK5 could identify clinically actionable proteins and provide a more mechanistic insight into ERK5 in the progression of PHGGS. To determine protein–protein associations (PPAs), we employed the proximity-dependent bio tin id entification (BioID2) method and generated inducible ERK5-BioID2 and ERK2-BioID2 constructs to overcome barriers of conventional screening methods for PPAs. ERK2, similar in structure but much more studied than ERK5, was used as a comparison. Using DIPG lines as proof of principle, we performed streptavidin pull down assays for putative biotinylated ERK PPA and followed with mass spectrometry to identify the ERK2 and ERK5 interactomes. RESULTS: Using data-dependent acquisition (DDA), we identified several unique and common interactors of ERK5 compared to ERK2. Through STRING network and pathway analysis, we identified a novel function of ERK5 with respect to membrane trafficking and vesicle transport. Identification of interactors with ERK5 may lead to effective therapeutic combinations. Our current work is focused on validating these interactions and the function of ERK5 in these biological processes. CONCLUSIONS: Currently, ERK5 is not as understood as ERK1 or ERK2. Identification of interactors and substrates of ERK5 will further our understanding of PHGG biology, and may lead to identifying druggable targets and pathways.